Potentially Inappropriate Medication Among People With Dementia in China: A Nationwide Cross-Sectional Study - Zhao, Mengnan; Chen, Zhaoyan; Tian, Fangyuan; Xu, Ting (Frontiers in Pharmacology, 2022)
Objectives: The purpose of this study was to explore the prevalence of potentially inappropriate medication (PIM) among older outpatients (age≥65 years old) with dementia from eight cities in China using the AGS Beers criteria of 2019 and to identify the potential factor increasing the number of PIMs. Methods: A cross-sectional study was carried out in eight cities in China, Chengdu, Beijing, Guangzhou, Shanghai, Shenyang, Tianjin, Zhengzhou, and Hangzhou, located in each direction from January 2020 to December 2020. Based on the 2019 AGS Beer criteria, the PIM prescriptions were evaluated. The identification of potential factors was completed using a binary logistic regression model. Results: Of 18624 older patients with dementia, 39.43% were detected with at least 1 PIM, and 36% received at least two PIMs. The antipsychotic drugs quetiapine and olanzapine were most frequently prescribed in patients with PIM, accounting for 8.01% and 7.36%, respectively. Logistic regression analyses showed female dementia patients aged >80 years who took more medications were exposed easily to PIM use. Conclusion: PIM use among older outpatients with dementia in China is highly prevalent, and the associated risk factors were increasing age, female sex, and number of medications. The most frequently prescribed drugs by clinicians were psychotropic drugs, which were much more frequent than other drugs.